Educación tributaria y el cumplimiento de las obligaciones tributarias de las mypes del distrito de Punchana año 2022 - San Roman Castro, Nelyt Rous Jenniffer (2023)
In the final report, the general objective is identified to determine the relationship between tax education and compliance with the tax obligations of the Mypes of the Punchana District in 2022; a descriptive - correlational research and non-experimental design; taking as a sample 132 Mypes who were used the survey technique and the questionnaire as an instrument. Therefore, it was concluded that tax education is rated as average by 24%, since they neither agree / disagree with personal values; as they are also in disagreement, since they consider that tax academic training courses should be taught; but they agree with the informative talks given by SUNAT regarding tax issues. Regarding compliance with tax obligations, it is rated as average (23%) because the state sometimes adequately allocates the taxes collected to public works; however, it always issues payment receipts. Managing to determine an existing relationship between tax education and compliance with tax obligations contrasted by a value and a considerable positive sig (r=0.718; p=0.000).